Discovery Learning in EFL Speaking Instruction: Its Impact on Ninth-Grade Students’ Speaking Skills - Fitria, Juwita Ramadani; Hidayat, Ayi Nazmul; Holik, Abdul (Journal of General Education and Humanities, 2026)
Speaking skills remain one of the most challenging aspects of English as a Foreign Language (EFL) learning for senior high school students, particularly in contexts where teacher-centered practices dominate classroom instruction. This study investigates the effectiveness of Discovery Learning in enhancing ninth-grade students’ speaking skills in an EFL classroom. Employing a quasi-experimental design, the study involved 60 students divided into an experimental group taught using Discovery Learning and a control group receiving conventional instruction. Students’ speaking performance was measured through pre-test and post-test speaking tasks assessed using an analytic speaking rubric covering fluency, pronunciation, vocabulary, grammatical accuracy, and confidence. The data were analyzed using paired-samples and independent-samples t-tests, complemented by effect size analysis. The results revealed a statistically significant improvement in the experimental group’s speaking performance, with a large effect size, indicating the strong impact of Discovery Learning. Further analysis showed that fluency and confidence experienced the greatest improvement. These findings suggest that Discovery Learning provides meaningful opportunities for active language use and supports both cognitive and affective dimensions of speaking development. The study contributes to EFL pedagogy by demonstrating the applicability of discovery-based instruction to speaking skills in senior high school contexts.